KEBERDAYAAN PETANI DALAM PENERAPAN BUDIDAYA PADI SAWAH SISTEM JAJAR LEGOWO DI DESA BABAKANKARET KECAMATAN CIANJUR KABUPATEN CIANJUR PROVINSI JAWA BARAT - Ahmad Hamdana; Dedy Kusnadi; Harniati Harniati (Sekolah Tinggi Pariwisata Mataram, 2020)
The empowerment of farmers in the application of the Legowo range must be increased. Farmer empowerment that has been applied in agricultural activities, especially in the cultivation of lowland rice is not appropriate and optimal. Therefore, farmer empowerment that includes knowledge, attitudes and skills must be improved to increase farmer productivity and income. This study aims to improve the empowerment of farmers in the application of the Legowo row system. This research was conducted in March-July 2020. The research location was determined intentionally in Babakankaret Village, Cianjur Regency, Cianjur Regency, West Java Province with a sample of farmers who cultivated lowland rice. Determination of selected population areas intentionally with the following criteria 1) potential area for lowland rice farming and the majority of the population involved in lowland rice, 2) farmer groups that have received the SL-PTT (Integrated Crop Management Field School) program, and 3) time, energy and cost constraints. The number of respondents was 49 farmers from three groups of farmers. Data collection is done through observation, questionnaire distribution, interviews, and literature studies. Descriptive analysis is used to explain farmer empowerment, regression analysis is used to find out the factors that influence each indicator in individual characteristics and counseling support for farmer empowerment in implementing the legowo line system, while W Kendall's analysis is used to determine priority issues made into counseling material or topic for increase the empowerment of farmers in the application of the Legowo row system. The results of the analysis show that the level of farmer empowerment is included in the medium category, and the area of ​​land from individual characteristic factors and the frequency of counseling from extension support has a significant effect on farmer empowerment. In designing strategies to increase the empowerment of farmers in the application of the Legowo row system, this is done by providing counseling to increase the frequency of counseling as well as providing suggestions for utilizing cultivated land to implement the Legowo row system.